LINKAGES BETWEEN BANK COMPETITION AND FINANCIAL STABILITY: A COMPARATIVE STUDY OF SHARIA VS CONVENTIONAL BANKING IN INDONESIA - Wahyudi, Setyo Tri; Badriyah, Nurul; Nabella, Rihana Sofie; Sari, Kartika; Radeetha, Radeetha (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
Banking is one of the most important sectors supporting a country"™s economy. In Indonesia, the development of banking has undergone significant changes, as evidenced by the shift from the conventional system to the dual banking and Sharia systems. The large number of commercial banks and bank offices suggests high competition in Indonesia. Consequently, banks must reduce costs and streamline their operational activities to remain competitive. This study aims to analyze the relationship between bank competition and financial stability in Indonesia for both conventional and Islamic banks, using the generalized method of moments. The results show a positive relationship between the level of banking industry competition and banking stability, indicating that an increase in bank competition will result in greater stability. These findings suggest that Islamic banking has the potential to expand its market share by improving its soundness and retaining customer loyalty. In addition, banking authorities should reevaluate their performance and regulations.JEL: G21, G32, L10.